DAB2IP inhibits glucose uptake by modulating HIF-1α ubiquitination under hypoxia in breast cancer - Dong, Hongliang; Jia, Weiyi; Meng, Weijian; Zhang, Rui; Qi, Zhihong; Chen, Zhuo; Xie, Sophia; Min, Jiang; Liu, Liang; Shen, Jie (Oncogenesis (New York, NY), 2024)
Metabolic reprogramming has become increasingly important in tumor biology research. The glucose metabolic pathway is a major energy source and is often dysregulated in breast cancer. DAB2IP is widely reported to be a tumor suppressor that acts as a scaffold protein to suppress tumor malignancy in breast cancer. Interestingly, DAB2IP has also been found to be a potential regulator of glucose uptake; however, the exact mechanism remains unclear. In this study, we found that DAB2IP inhibited glucose uptake under hypoxia conditions in breast cancer cells by suppressing HIF-1α signals. Mechanically, DAB2IP interacted with the E3 ubiquitin ligase STUB1 via its PER domain, thus triggering STUB1 mediated HIF-1α ubiquitylation and degradation, and inhibit glucose metabolism and tumor progression. Deleting the PER domain abrogated the DAB2IP-related inhibitory effects on glucose uptake, intracellular ATP production, and lactic acid production in breast cancer cells. These findings elucidate the biological roles of DAB2IP in cancer-related glucose metabolism as well as a novel mechanism by which STUB1-driven HIF-1α ubiquitylated degradation is regulated in breast cancer.